The novel adjuvant dmLT promotes dose sparing, mucosal immunity and longevity of antibody responses to the inactivated polio vaccine in a murine model. Issue 16 (15th April 2015) - Norton, Elizabeth B.; Bauer, David L.; Weldon, William C.; Oberste, M. Steven; Lawson, Louise B.; Clements, John D.
Highlights We evaluated the adjuvant dmLT admixed with inactivated poliovirus vaccine (IPV). Fractional IPV doses were delivered intramuscularly or intradermally in mice. dmLT adjuvant enables dose-sparing of IPV, particularly for serotype-1. dmLT enhances mucosal immunity and longevity of serum anti-PV neutralizing titers.